Effectiveness and Applications of Medical Treatments Utilizing Infrared Radiation - Faleh, Mohammed Sabah; Ayet, Aya Kreem; Dalya Salah Hadi; AlZahra, Falah Hasan Abd (Innovative: International Multidisciplinary Journal of Applied Technology (2995-486X), 2024)
The idea of using infrared radiation as a treatment is a concept that dates back to the ancient Greeks and Egyptians. Practices of using thermal waters and sunshine for treating skin diseases date back to these periods. In today's medical field, various forms of infrared therapies are used as isolated treatments or as part of a multi-disciplinary approach. The idea of "heat" as a treatment can provide elaboration into the historical use of thermal spas. Intensive research is done on the skin and wound healing applications of infrared radiation, especially the lower parts of it. The application of infrared radiation in medicine is of great importance in today's medical practice. The use of this form of energy in therapy often comes in the form of a multi-disciplinary approach, which includes treatments from general practitioners as well as complementary therapists.